Edaphic arthropods during organic matter decomposition (2013)
In agroforestry systems tree pruning is a source of nutrients for the main crops, which makes it important to determine the decomposition rate of these residues. Among the factors influencing plant material decomposition, soil fauna plays an outstanding role. Thus, the relation between these two param- eters was the objective of the current work. The evaluation made use of litter bags filled with 50 g of leaves of gliricídia or ingá and scattered on the ground of an agroforestry system. These materials were collected on days 8, 14, 20, 27, 41, 57 and 78 after setting the experiment, plus two additional ingá sample collections on days 128 and 239. After collection, dry matter content and arthropod fauna (using Berlese-Tüllgren funis and laboratory screening) associated to plant material in each bag were determined. Gliricídia showed an increase in fauna abundance since day 14, to decline after day 41. In the case of ingá, fauna only increased after day 57. Soil fauna was observed to vary during the decomposition process and as a function of plant species decomposition rate, polyphenol content being the most influencing factor. While not all faunal groups accompanied the decomposition process, Isopoda was the one that most closely did so.